‘Milenial Bicara Anti-Korupsi’ Media and Youth Anti-Corruption Movement - Saef Andrian; Adinda Khairun Nisa; Nicka Tri Mulyasari; Adi Rahmanto; Nazela Fossy Noer Oemardhi (Indonesia Media Law Review, 2022)
Corruption is any type of activity based on dishonesty by taking advantage of the position or power held in order to obtain benefits for individuals or other people. In Indonesia itself, it is so synonymous with the problem of corruption, as well as corruption which is identical with Indonesia. This seems to illustrate the impression that Indonesia and corruption are two things that cannot be separated. The problem related to corruption that occurs in Indonesia is indeed quite alarming, the article is that criminal cases of corruption in Indonesia occur non-stop from year to year, almost every year new corruption cases appear with old or new figures. Corruption can be likened to a disease that gnaws at the mentality of Indonesians that seems difficult to treat. Therefore, it is important to change the mindset of the millennial generation from now on to increase awareness of the importance of anti-corruption because the future of Indonesia lies in the current millennial generation. The millennial generation has an important role in reducing and eradicating criminal acts of corruption, therefore, in order for that role to be real, it is necessary to provide training for the millennial generation in fighting corruption in the present or in the future.